THE EFFECT OF APPLYING COOPERATIVE LEARNING MODEL ON KNOWLEDGE COMPETENCE: LITERATURE STUDY ABOUT THINK TALK WRITE - Faren Landysa; Heffi Alberida; Ardi Ardi; Rahmadhani Fitri (Universitas Negeri Padang, 2021)
This research is motivated by learning that is still teacher-centered, students are not actively involved and do not take learning activities seriously. Learning using the lecture and discussion method, but in practice students do not understand the steps of the activity method used. At the time of learning, many students carry out activities outside of learning activities. Students do not concentrate on listening to the teacher's explanation and there is no collaboration between students and other students. So that the low competence of learning science students both in the aspects of knowledge, attitudes and skills. Efforts that can be made are applying the Think Talk Write type of cooperative learning model. Think Talk Write learning model is a learning model that can develop students' thinking, speaking and writing skills. This study aims to determine the effect of implementing the Think Talk Write type of cooperative learning model on students' science learning competencies. This research was conducted by reviewing several national-scale journals in Indonesia. The journal used is a journal that has 5 ISSN journals. The results obtained from the journal review are that there is a correlation between the application of the Think Talk Write type cooperative learning model to the science learning outcomes of students. This is evidenced by research conducted by Daha (2018), Sari (2017), Hulu (2019), Fitriana (2017), Erlija (2018) which uses a cooperative learning model type Think Talk Write assisted by media in learning.